Rapid protection against viral infections by chemokine-accelerated post-exposure vaccination - Heine, Annkristin; Lemmermann, Niels A. W.; Flores, Chrystel; Becker-Gotot, Janine; Garbi, Natalio; Brossart, Peter; Kurts, Christian (Frontiers in Immunology, 2024)
Introduction: Prophylactic vaccines generate strong and durable immunity to avoid future infections, whereas post-exposure vaccinations are intended to establish rapid protection against already ongoing infections. Antiviral cytotoxic CD8 + T cells (CTL) are activated by dendritic cells (DCs), which themselves must be activated by adjuvants to express costimulatory molecules and so-called signal 0-chemokines that attract naive CTL to the DCs.Here we asked whether a vaccination protocol that combines two adjuvants, a toll-like receptor ligand (TLR) and a natural killer T cell activator, to induce two signal 0 chemokines, synergistically accelerates CTL activation.We used a well-characterized vaccination model based on the model antigen ovalbumin, the TLR9 ligand CpG and the NKT cell ligand α-galactosylceramide to induce signal 0-chemokines.Exploiting this vaccination model, we studied detailed T cell kinetics and T cell profiling in different in vivo mouse models of viral infection.We found that CTL induced by both adjuvants obtained a head-start that allowed them to functionally differentiate further and generate higher numbers of protective CTL 1-2 days earlier. Such signal 0-optimized post-exposure vaccination hastened clearance of experimental adenovirus and cytomegalovirus infections.Our findings show that signal 0 chemokine-inducing adjuvant combinations gain time in the race against rapidly replicating microbes, which may be especially useful in post-exposure vaccination settings during viral epi/pandemics.